Efforts to Enhance Character of Responsibility and Self-Confidence in Numeracy Learning - Eva Nirtha; Ermelinda Agnes Gunu Pure; Arfiani Arfiani; Gunawan Gunawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research aimed to improve the character of responsibility and confidence of students in numeracy learning in the Elementary School Teacher Education Study Program (PGSD). The problems found in the numeracy learning process show that some students still lack a sense of responsibility for academic tasks and lack confidence in coming up with ideas and solving numeracy problems. This research uses the Classroom Action Research (PTK) approach which is carried out in two cycles which include the planning, action implementation, observation, and reflection stages. The research subjects were PGSD students who took numeracy learning courses. Data collection techniques are carried out through observation, documentation and reflection. Meanwhile, data analysis uses quantitative and qualitative descriptive analysis. The results of the study show that the application of active, creative and reflective numeracy learning strategies intervention is able to increase students' character of responsibility and confidence. This can be seen from the increase in student participation in discussions, accuracy in completing assignments, and the courage to express opinions during the learning process. The percentage of students' character responsibility and confidence increased with each research cycle. Thus, it can be concluded that the implementation of numeracy learning that is actively designed, creative and reflective, can increase the character of responsibility and confidence of PGSD students.